(A Finite Element Framework For Modeling Stimulated Raman And Brillouin Scattering In Application-Specific Plasmas In 3D) (International Journal of Environmental Sciences, 2025)
This numerical analysis successfully proves the efficient reduction of the gains of the numerically simulated parametric instabilities of laser-plasma interaction phenomena like Stimulated Raman Scattering and Stimulated Brillouin Scattering due to higher electron temperatures and a unique geometrical setup for laser propagation. With a complex numerical analysis technique, it can be shown that by increasing the electron temperature to 5.0 keV with a shorter propagation length of 50 µm, an efficient reduction of the parametric instabilities can be obtained while also sustaining a high level of coupling between the laser-plasma interaction. At an Nd: YAG laser with a wavelength of 1.06 µm and intensity of 10¹⁶ W/cm², a highly efficient reduction of the gains of SRS from 38.8 to 4.00 and that of SBS from 21.5 to 3.20 can be obtained. A unique range of operation for efficient reduction can exist for temperatures higher than 3 Kev. This technique of reducing parametric instabilities can be named as a promising one for controllable parametric processes of laser-plasma interaction with a temperature control technique.